2001
DOI: 10.1086/322773
|View full text |Cite
|
Sign up to set email alerts
|

Blue Stragglers, Young White Dwarfs, and UV‐Excess Stars in the Core of 47 Tucanae

Abstract: We used a set of archived HST/WFPC2 images to probe the stellar population in the core of the nearby Galactic Globular Cluster (GGC) 47 Tuc. From the ultraviolet (UV) Color Magnitude Diagrams (CMDs) obtained for ∼ 4 000 stars detected within the Planetary Camera (PC) field of view we have pinpointed a number of interesting objects: (i) 43 blue stragglers stars (BSSs) including 20

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
122
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 97 publications
(129 citation statements)
references
References 39 publications
7
122
0
Order By: Relevance
“…In particular, we have studied the potential NF population in 47 Tuc, which is both less dense and more massive than NGC 6397, and for which a wealth of observational data is becoming available. In this Ferraro et al (2001aFerraro et al ( , 2001b. Open circles and triangles denote blue stragglers and normal white dwarfs, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, we have studied the potential NF population in 47 Tuc, which is both less dense and more massive than NGC 6397, and for which a wealth of observational data is becoming available. In this Ferraro et al (2001aFerraro et al ( , 2001b. Open circles and triangles denote blue stragglers and normal white dwarfs, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…In what follows, we discuss our expectations for the (currently undetected) NF population in 47 Tuc. The attraction of this cluster is the rich data set spanning X-ray (Grindlay et al 2001a), UV (Ferraro et al 2001b;Knigge et al 2002), optical (Gilliland et al 2000), and radio (Camilo et al 2000) wavelengths. 47 Tuc is also interesting in that it is a dense, pre-core-collapse cluster and somewhat more massive than NGC 6397.…”
Section: Application To 47 Tucmentioning
confidence: 99%
“…Using the procedure described in Ferraro et al (2001Ferraro et al ( , 2003) the WFI catalog has been placed on the absolute astrometric system. The eight WFI CCDs have been astrometrized by crosscorrelating each of them with the new astrometric Two Micron All Sky Survey (2MASS) catalog using a specific tool developed at Bologna Observatory.…”
Section: Astrometry Photometric Calibration and Sample Definitionmentioning
confidence: 99%
“…At the end of the procedure the rms residuals (which we take as representative of the astrometric accuracy) were of the order of $0.3 00 both in right ascension and declination. By using the procedure described in Ferraro et al (1997Ferraro et al ( , 2001), the photometric calibration of the UV magnitudes (F255W and F336W ) has been performed in the STmag system, adopting the Holtzman et al (1995) zero points. The optical (B and V ) magnitudes have been transformed to the Johnson system by using the stars in common with the catalog of Piotto et al (2002).…”
Section: Astrometry Photometric Calibration and Sample Definitionmentioning
confidence: 99%
“…The first evidence of the presence of a BSS bimodal distribution (Ferraro et al 1997) was found in M 3 and was later on confirmed for other clusters: M 55 (Zaggia et al 1997); 47 Tuc (Ferraro et al 2001); Pal 13 (Clark et al 2004); NGC 6752 (Sabbi et al 2004); M 5 (Warren et al 2006); and M 62 (Beccari et al 2006), while in ω Cen the bimodality seems to be ruled out .…”
Section: Article Published By Edp Sciencesmentioning
confidence: 79%